Early-Life Stress Induces Depression-Like Behavior and Synaptic-Plasticity Changes in a Maternal Separation Rat Model: Gender Difference and Metabolomics Study - Cui, Yongfei; Cao, Kerun; Lin, Huiyuan; Cui, Sainan; Shen, Chongkun; Wen, Wenhao; Mo, Haixin; Dong, Zhaoyang; Bai, Shasha; Yang, Lei; Shi, Yafei; Zhang, Rong (Frontiers in Pharmacology, 2020)
More than 300 million people suffer from depressive disorders globally. Studies have shown that people under early-life stress (ELS) are vulnerable to depression in their adulthood, and synaptic plasticity can be the molecular mechanism underlying depression. This study simulated ELS by using a maternal separation (MS) model, and the behavior of Sprague–Dawley (SD) rats in adulthood were evaluated through behavioral examination, including sucrose-preference, forced-swimming, and open-field tests. The behavior tests showed that SD rats in the MS group were more susceptible to depression-like and anxiety-like behavior than those inof the non-MS (NMS) group. Nissl staining analysis indicated a significant reduction in the number of neurons at the prefrontal cortex and hippocampus including the CA1, CA2, CA3, and DG regions of SD rats in the MS group. Immunohistochemistry results showed that the percentages of synaptophysin positive area in the prefrontal cortex and hippocampus (including the CA1, CA2, CA3, and DG regions) slice of the MS group were significantly reduced compared with those of the NMS group. Western blot analysis was used to assess synaptic plasticity protein markers, including PSD-95, SYN, and GAP-43 protein expression in the cortex and hippocampus. Results showed that the expression levels of these three proteins in the MS group were significantly lower than those in the NMS group. No significant difference was observed in the peak areas of sex hormones and their metabolites including estradiol, testosterone, androstenedione, estrone, estriol, and 5β-dihydrotestosterone by LC–MS/MS detection. Through the application of nontargeted metabolomics to the overall analysis of differential metabolites, pathway-enrichment results showed the importance of arginine and proline metabolism, pantothenate and CoA biosyntheses, and glutathione metabolism, as well as the phenylalanine, tyrosine, and tryptophan biosynthesis pathways. In summary, the MS model caused adult SD rats to be susceptible to depression, which may regulate synaptic plasticity through arginine and proline metabolism, pantothenate and CoA biosyntheses, glutathione metabolism, and phenylalanine, tyrosine, and tryptophan biosyntheses.